COMPARATIVE DESCRIPTION OF CYTOPENIC SYNDROME IN VIRUS ETIOLOGY LIVER CIRRHOSIS - Z.A, Sayfiddinova; Islamova Z.S; Slamova G.E; Adilov A.A.; Saidmurodov B.S; Nurillayeva G.S (PT. Antis International Publisher, 2024)
General Background: Liver cirrhosis is a severe complication of chronic viral hepatitis, significantly impacting hematological parameters and leading to cytopenic syndromes. Specific Background: While both Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) are known to cause liver cirrhosis, the comparative hematological features associated with these viral etiologies remain inadequately explored. Knowledge Gap: Current literature lacks comprehensive analysis on the differences in cytopenic manifestations in patients with liver cirrhosis of HBV versus HCV origin. Aims: This study aims to evaluate and compare the cytopenic syndromes present in patients with liver cirrhosis attributed to HBV and HCV, with a focus on blood parameters, coagulation factors, and protein fractions. Results: The analysis included 50 patients diagnosed with viral etiology liver cirrhosis. Findings revealed significant decreases in blood platelets, blood coagulation factors, and protein fractions, alongside the presence of hemorrhagic syndromes of various origins. Novelty: This study provides a comparative perspective on the hematological implications of liver cirrhosis due to HBV and HCV, highlighting specific deficiencies in blood components linked to each viral etiology. Implications: Understanding the distinct cytopenic features in liver cirrhosis patients with HBV and HCV may guide more tailored clinical management strategies and improve patient outcomes by addressing the unique hematological challenges associated with each viral infection